The genus Megaleuctra Neave (Plecoptera: Leuctridae) in North America - Baumann, Richard W. (Illiesia, 2013)
The extant Nearctic Megaleuctra are reviewed and five species are recognized: M. complicata Claassen, M. flinti Baumann, M. kincaidi Frison, M. stigmata (Banks), and M. williamsae Hanson. Diagnostic illustrations and SEM images are provided for the male and female of all species. The females of M. complicata and M. flinti are described for the first time and M. sierra Fields is placed as a synonym of M. stigmata.
Keywords: entomology; Leuctridae; Megaleuctra; Plecoptera; stoneflies; North America; United States of America; USA